Diagenetic Heterogeneity of Deep Sandstones and Its Relationship to Oil Emplacement: A Case Study from the Middle Jurassic Toutunhe Formation in the Fukang Sag, Central Junggar Basin (NW China). (25th September 2017) - Cao, Binfeng; Luo, Xiaorong; Zhang, Likuan; Sui, Fenggui; Lin, Huixi; Lei, Yuhong
Abstract : The Middle Jurassic Toutunhe Formation at depths of approximately 4000–6000 m has increasingly come into focus as a current deep reservoir target in the central Junggar Basin (NW China). Based on petrography, SEM, stable isotopes, and fluid inclusion analyses, the goals of this study were to investigate the effect of depositional lithofacies on sandstone diagenetic heterogeneity and to examine the relationship between diagenetic evolution and oil charge within a heterogeneous reservoir. Grain size controls the overall abundance of cement and porosity and reservoir properties through its effect on ductile lithic sand grains and hence on mechanical compaction. Early diagenetic calcite cement is an exception to this trend. Ductile lithic-rich, very fine-grained sandstones featured compaction of easily deformed, clay-rich grains, resulting in a very rapid loss of porosity during burial. In contrast, dissolution and cementation occurred as well as ductile compaction in the fine-grained sandstones. Two episodes of oil charge occurred in the relatively coarser-grained sandstone lithofacies. Diagenesis progressed alternately with oil emplacement, and some diagenetic alterations and oil charge occurred simultaneously. Ductile lithic-rich, highly compacted sandstones and tightly calcite-cemented sandstones can create permeability barriers embedded in permeable reservoir sandstones, probably resulting in heterogeneous flow.